From Ethnic Genealogical Folklore to the Power and Legitimacy of Traditional Society - Leylia Khairani; Ketut Wiradnyana (Green Publisher Indonesia, 2023)
The folklore of the genealogical origin of an ethnicity is a very popular cultural treasure for the Gayo, Nias, and Batak Toba ethnic communities, especially those related to genealogy. The original characters of the ethnic community are depicted falling from a high place (heaven) to a low place (bumi). The events of the story characters coming down from the sky make the figure genetic, and the region has a very important power value in its supportive ethnic society. Folklore stories of the genealogical origins of these three ethnicities will be analysed through the meaning patterns that are the guidelines of life for the ethnic community. Given the folklore of the genealogical origins of the three ethnic groups, they are closely linked to the system of power in ethnic societies. The study aims to explore how meaning patterns are operated in order to safeguard, maintain, and stabilise the power of individuals as well as ethnic groups. As for the research methods used in this research, they use archaeological, anthropological, ethno-archaeological, and sociological approaches. The results achieved in the folklore study of ethnic genealogical origin depict the system of power in the cultures of the ethnic communities Batak Toba, Nias, and Gayo.